MORPHOLOGICAL CHARACTERISTICS AND ION CONCENTRATIONS OF GRAFTED AND NON-GRAFTED EGGPLANT SEEDLINGS UNDER DROUGHT AND SALT STRESS - S. Kran; S. Ku_vuran; C. Ate_; K. Sönmez; ^. ^. Ellialtiolu (Journal of Animal and Plant Sciences, 2018)
The performance of 4 eggplant genotypes grafted on the salt-tolerant rootstocks under drought and salt stress conditions was evaluated at the seedling stage in a hydroponic system. Four eggplant scion genotypes (Salt-tolerant: Mardin K1z1ltepe,Burdur Merkez; Salt-sensitive: Artvin Hopa and Kemer) and 2 rootstocks (Köksal-F , Vista-306) were 1 selected for the study. Drought and salt treatments were applied to all materials separately. Drought stress (D ) was 1 created by adding 15% (w/v) PEG-6000 to growth ambient growth solution. PEG was not added to the growth solution of control plants (D ). For salt stress (S ), 100 mM NaCl was added to the growth solution and salt was not added to 0 1 control plants (S ). Stress-induced variations in shoot-root fresh and dry weights, relative water contents and ion 0 concentrations were investigated. With regard to investigated parameters, differences were observed between rootstock/scion combinations. Grafted plants showed significantly superior performance against drought and salt stress. The rootstock Köksal-F resulted in greater resistance to drought and salt stress. The grafted plants had higher shoot-root 1 +2 + fresh and dry weights, relative water contents and shoot-root Ca and K concentrations than non-grafted plants under + - both stress conditions. The grafted plants also had less reductions in Na and Cl accumulation under salt stress. over rootstocks, can be used to increase resistance to
Keywords: Solanum melongena; salinity; drought; grafting; ion.